Gimnasia educativa básica - Mamani-Jilaja, Dometila (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
The book was adapted from an investigation whose objective was to determine the effect of the application of the DEPREPCEP Program in the learning of Basic Gymnastics in girls from the Gymnastics League of Puno (Perú). The study was an experimental application type, with a pre- and post-test design of a single group. The study population was 60 girls and the sample was 30 girls from the Puno Gymnastics League. For data collection, the Gymnastics Checklist was used as an instrument. For data analysis, percentage statistics were applied and to test the hypothesis, the T Student statistical test, and as a result, in the gymnastic program, 100% obtained a bad grade in almost all the basic gymnastics exercises before the application of the program. and after application of the program the performance of these gymnastic exercises is performed excellently in more than 50% of the girls. Comparing these results with the evaluation after the application of the DEPREPCEP Program, learning improves significantly. With the Student's t-test, the proposed hypothesis is confirmed, because it has been verified that there are significant differences (p=0.000) between the results of the pre-test and post-test. Therefore, the application of the DEPREPCEP Program has a significant effect on the learning of Basic Gymnastics in girls from the Puno Gymnastics League. In conclusion, the DEPREPCEP Program improves the performance capacity and physical strengthening of the organism in girls.